Waste to Valuable By-product: Palm Oil Mill Decanter Cake and its Ability to Remove Cd, Cu and Pb Ions - Nugroho, Dewayanto; M. Z., Sahad; Mohd Ridzuan, Nordin (2009)
Palm oil mills generate about 4 - 5 tons of decanter cake for every 100 tons of palm fresh fruit bunch processed. Due to the high organic content, the decanter cake could be converted into adsorbent for the removal of metal ions from waste water. The decanter cake was first dried at 105 oC and then carbonized at various temperatures. The resulting carbonized decanter cake were tested for removing cadmium (II), copper (II), and lead (II) ions. Proximate analysis using thermogravimetry of decanter cake carbonized at 500 oC indicated that the adsorbent contained 4% moisture, 21% volatile,23% fixed carbon, and 52% ash. Adsorption test was carried out by mixing 1.0 g of the decanter cake in 100 mL aqueous solution of the various ions. The concentration of metal ions in the solutions used is in the range of 100 – 1000 mg/L. The results of adsorption studies indicated that the removal of metal ions was highest in the case of Pb when the carbonization temperature was 500 oC and 600 oC in the case of Cd and Cu. Maximum removal of the Cd, Cu and Pb were also observed to take place when the pH of the solution is in the range of 4 – 5. Langmuir and Freundlich isotherm models were used to fit the isotherm experimental data. The maximum uptakes of Cd, Cu and Pb onto the carbonized decanter cake in this study were estimated to be 24, 23, and 97 mg/g respectively. The ability of the carbonized decanter cake to remove the metal ions was found to be comparable to that of other adsorbents derived from agricultural waste.